Associate Issues in Delayed Care Seeking Behavior in Households Suffering from Malaria - Ogali, Ugo; Otu, Judith E.; Enang, Ebingha E.; Angioha, Pius U.; Akande, Depoe (ARRUS Journal of Mathematics and Applied Science, 2022)
this study examines the associated issues in delayed care-seeking behaviour from malaria in households in rural Central Cross River states. Specifically, this study examines the extent to which belief in traditional medicine and household income relates to delayed care-seeking behaviour in household members suffering from malaria. The descriptive survey method was utilized to collect data from 1,229 participants from Central Cross River State, Nigeria. 1,224 The participants were selected using the multistage sampling technique. Data was collected using a self-developed structured questionnaire and in-depth interview guide. Elicited data was analyzed using descriptor and parametric statistics. Data collected from the in-depth interview conducted on five participants in the study area were thematically analyzed. Out of the 1224 quantitative instrument distributed, 1065 was judged to valid to the researchers. The analysis revealed that belief in traditional medicine and household income were significant determinants of delay in care-seeking behaviour among grow household members suffering from malaria. The study calls for policy change towards malaria care for rural households in Central Cross River states.